2016
DOI: 10.4102/phcfm.v8i2.1002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices regarding cervical cancer prevention at Thulamela Municipality of Vhembe District in Limpopo Province

Abstract: BackgroundCervical cancer is a widespread and often fatal disease that affected 1 million women globally in 2005. Not only is it the second most common cancer in women but it was also the second leading cause of cancer deaths, accounting for over 250 000 in 2006.PurposeThe purpose of the study was to assess the knowledge, attitudes and practices regarding cervical cancer prevention among rural women in Vhembe District in Limpopo Province.MethodologyA quantitative descriptive approach was adopted. The quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
1
11
0
2
Order By: Relevance
“…Cervical cancer screening services could be utilized better if cervical cancer screening awareness campaigns were sustained and the services were accessible, affordable and available [20]. Previous findings revealed that women in this setting, lacked knowledge about cervical cancer and the prevention thereof, but displayed positive attitudes to the utilisation of cervical cancer screening services [27]. Women who did not know what a Pap smear was would not even know that with any gynecological complaints, such as, pain, bleeding, offensive discharges or loss of weight, a Pap smear would be required as part of the routine gynecological examination [28].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cervical cancer screening services could be utilized better if cervical cancer screening awareness campaigns were sustained and the services were accessible, affordable and available [20]. Previous findings revealed that women in this setting, lacked knowledge about cervical cancer and the prevention thereof, but displayed positive attitudes to the utilisation of cervical cancer screening services [27]. Women who did not know what a Pap smear was would not even know that with any gynecological complaints, such as, pain, bleeding, offensive discharges or loss of weight, a Pap smear would be required as part of the routine gynecological examination [28].…”
Section: Discussionmentioning
confidence: 95%
“…This is confirmed by Kim et al [36] who revealed that knowledge and low-risk perceptions of cervical cancer were the most important barriers to screening; these barriers discourage women from utilising cervical cancer screening services. In order to change the attitude of women, health messages should be formulated to address specific areas [27,37].…”
Section: Discussionmentioning
confidence: 99%
“…(14) Güney Afrika'da 30 yaş ve üzerindeki 1.546 kadın ile yapılan araştırmada katılımcıların %62'sinin servikal kanserler konusunda yeterli bilgisinin olmadığı; bilgi sahibi olanların da sadece %51'inin sağlık personeli tarafından bilgilendirildiği sonucuna ulaşılmıştır. (15) Araştırmamızda yaptığımız kısa bilgilendirmeden sonra serviks ve meme kanseri taraması yaptırmak isteyenlerin oranı artarken akciğer, kolorektal kanser ve prostat kanseri taraması yaptırmak isteyenler sayıca azalmıştır. Eğitimle serviks ve meme kanserinin erken tanısının taramalarla yapılabileceğinin öğrenilmesi tarama isteğinin artış nedeni olabilir.…”
Section: Discussionunclassified
“…(7) In the study conducted by Ramatuba and colleagues in Africa, the participants in the study found that they had incomplete information about cervical cancer and its screening. (8) In a study conducted by Şahin Ş in the central district of Aydın, it was concluded that the people who applied to the family medicine outpatient clinic had insufficient knowledge about colon cancer screening and therefore they did not have cancer screening. (9) Pehlivanoğlu et al, found that among women who applied to the family medicine outpatient clinic those who have had a gynecological examination have a statistically significantly higher rate of cervical cancer screening than those who did not have a gynecological examination.…”
Section: Discussionmentioning
confidence: 99%